Research on the Diffusion of Vs55 Permeability in Rat Kidneys Based on Computer Tomography - Liu Ke; Xu Yi; Feng Haikao; Dang Hangyu; Yang Guoliang; Li Xin (Zhileng xuebao)
Cryopreservation is the usual method for long-term preservation of natural and engineered tissues. However, homogeneous loading of tissues with CPAs constitutes one of the major hurdles in tissue cryopreservation. In this study, computer tomography (CT) was used as a non-invasive imaging method to determine the effective diffusion of Vs55 in tissue-engineered collagen scaffolds, and the effective diffusion constant (Deff) was calculated by the theoretic model. The kidney activation energy was calculated according to the effective diffusion constant obtained by CT. The results demonstrated that the higher the loading concentration, the faster the rate of diffusion. When Vs55 concentration was 8.4 mol/L, the diffusion rates were 1.77××10-6cm2/s at 4 °C,2.94××10-6cm2/s at 22 °C, and 3.93××10-6cm2/s at 37 °C, respectively. The model was demonstrated to predict the spatial and temporal distribution of Vs55 in the kidney. The coefficient of determination (R2) and the mean relative error (MRE) were 0.960–0.993 and 3.07%–6.74%, respectively. This observation was temperature-dependent, with slower permeation at lower temperatures. This study demonstrated the effectiveness of CT to measure Vs55 permeation into rat kidney.